Association of human immunodeficiency virus and hepatitis C virus infection with long-term outcomes post-ST segment elevation myocardial infarction in a disadvantaged urban community. (October 2020) - Shitole, Sanyog G.; Kuniholm, Mark H.; Hanna, David B.; Boucher, Thomas; Peng, Angel Y.; Berardi, Cecilia; Shah, Tina; Bortnick, Anna E.; Christia, Panagiota; Scheuer, James; Kizer, Jorge R.
Abstract: Background: HIV and HCV have been linked to an increased risk of cardiovascular disease (CVD). Their impact on long-term outcomes following ST-segment myocardial infarction (STEMI) has not been previously studied. Methods: We leveraged data from a STEMI registry (n = 1208) at an inner-city health system to assess the influence of HIV and HCV on post-STEMI outcomes. Cox regression was used to compare HIV-monoinfected (n = 22), HCV-monoinfected (n = 26) and HIV-HCV-coinfected patients (n = 8) with the neither-infected group (n = 1152) with regard to death, death or any readmission, and death or CVD readmission. Results: The cohort was majority black or Hispanic. Median follow-up was 4.3 years. Compared to the neither-infected group, the HIV-monoinfected group showed near-significantly higher risks of death or any readmission (HR = 1.62, 95% CI = 0.96, 2.74) and death or CVD readmission (HR = 1.82, 95% CI = 0.98, 3.39) after full adjustment. On similar comparison, the HCV-monoinfected group exhibited significantly higher risks of death (HR = 2.09, 95% CI = 1.05, 4.15) and death or any readmission (HR = 1.68, 95% CI = 1.07, 2.65), whereas the HIV-HCV-coinfected group showed higher risk of death (HR = 6.51, 95% CI = 2.28, 18.61). Conclusions: In this cohort composed mostly of race-ethnic minorities, HIV monoinfection tended to be associated with 1.6-to-1.8-fold higher risk of death or readmission for any cause or CVD over long-term follow-up compared to neither infection, whereas HCV monoinfection was associated with 1.7-to-2.1-fold higher risk of death and death or any readmission, and HIV-HCV coinfection with 6.5-fold higher risk of death. These associations require further study in larger populations, but highlight the importance of identifying and treating HIV and HCV in patients presenting with STEMI. Graphical abstract: Image 1 Highlights: In a low-income population, HIV and HCV were associated with adverse outcomes post-STEMI during long-term follow-up. Given availability of effective direct acting antivirals, HCV screening and treatment should be prioritized in STEMI In light of the benefits of antiretroviral therapy, appropriate screening and management of HIV in STEMI merit emphasis